Leadership, Organizational Climate and Maturity Levels of Patient Safety Culture on Nurses' Work Engagement - Jenmi Silaen; Rokiah Kusumapradja; Rina Mutiara (International Journal of Nursing and Health Services (IJNHS), 2023)
Background. Work engagement is a positive feeling, motivation, and work related to a psychological state characterized by enthusiasm, dedication, and appreciation. Objective: The purpose of this study was to analyze the influence of leadership, organizational climate, and the level of maturity of patient safety culture simultaneously or individually on nurses' work engagement. Method: This study uses a quantitative approach with an explanatory causality research design. Collecting data was collected using a questionnaire and tested using Multiple Linear Regression Analysis. Results: The results found that leadership, organizational climate, and the level of maturity of patient safety culture simultaneously and partially affected work engagement. However, leadership somewhat affects work engagement, while organizational climate and maturity level of patient safety culture does not affect work engagement. Conclusion and Recommendation: This research helps hospital management in developing a policy system for making regulations that can be started from the bottom up, with nurses being involved in easy decision-making as well as completing standard operating procedures in their work units